Navigating the Commodity Rollercoaster: Efficiency, Firm Size and Profitability in Mining Manufacturing under Price Volatility (2020-2024) - Salsabila, Annisa; Widajatun, Vincentia Wahju (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study analyzes the profitability of mining manufacturing companies in Indonesia, focusing on the period of high commodity price volatility from 2020 to 2024. The objective is to examine the influence of operational efficiency and firm size on profitability (EBITDA Margin), as well as the moderating role of commodity price volatility in this relationship. The method used is quantitative, with panel data from 53 companies listed on the Indonesia Stock Exchange (IDX), analyzed using panel data regression with the Fixed Effects model. The results prove that operational efficiency has a negative effect on profitability, and firm size also has a negative effect on profitability. Commodity price volatility strengthens the positive effect of operational efficiency but, conversely, weakens the negative effect of firm size on profitability. In times of price uncertainty, operational efficiency becomes a more crucial factor in determining profitability resilience than the size of the firm.